Market surveys: Barotse floodplain system - Pasqualino, M.; Kennedy, G.; Nowak, V. (Bioversity International, 2015)
The aim of the CGIAR Research Program on Aquatic Agricultural Systems (AAS) is to improve livelihoods and food security by enhancing the productivity and diversity of aquatic and agricultural systems. The AAS program in the Barotse floodplain of Zambia, which is being implemented in ten communities including; Kabula, Kapanda Lealui, Mapungu, Mwandi, Nalitoya, Nembwele, Senanga, Sifuna and Situlu in December 2014, in Nanikelako in April 2015 and in Mwandi, evaluates changes in seasonal flooding patterns and the availability of natural resources to strengthen the productivity of aquatic agricultural management practices and improve the livelihoods of the poor and vulnerable.